Nivolumab-induced subacute cutaneous lupus erythematosus in a patient with sigmoid colon cancer: a case report and review of the literature - Chang, Li; Zhang, Jianglin; Sun, Zhaojun; Zhou, Youyou; Zheng, Lixiong (Frontiers in Oncology, 2025)
IntroductionImmune checkpoint inhibitors (ICIs) are widely used in the treatment of various cancers, but they may lead to multi-system immune-related adverse events (irAEs). Subacute cutaneous lupus erythematosus (SCLE) has rarely been reported, however, it can cause severe adverse cutaneous reactions, which then affect patients’ anti-tumor treatment decisions as well as life and survival. This study presented the first case report of SCLE caused by nivolumab in the patient with sigmoid colon cancer, and summarized the clinical manifestations, diagnostic criteria and specific treatment plans of this type of disease.Case presentationAfter the treatment of sigmoid colon cancer with nivolumab, a 72-year-old male patient developed multiple well-demarcated erythematous annular plaques on the upper trunk and dorsal forearm, with erythematous borders and central clearing. The infiltrating erythema was observed behind the ear and in the occipital area on both sides, with thin scales attached and gradually increasing. Serum laboratory testing indicated an elevated anti-nuclear antibody (ANA) titer, strong positive for Sjogren’s syndrome-A (SS-A)/Ro and Sjogren’s syndrome-B (SS-B) antibodies. The pathological result of skin biopsy suggested SCLE. In terms of treatment, the patient’s rash was significantly improved after suspending the treatment of nivolumab and adding methylprednisolone and hydroxychloroquine. At present, the patient survived and the rash was stable after seventeen months of follow-up.ConclusionThrough the discussion of this case, the typical characteristics, diagnostic criteria and treatment of DI-SCLE caused by ICIs are summarized in detail, which provides help for early clinical diagnosis and effective management of DI-SCLE caused by ICIs, and effective treatment is expected to prolong the survival period and improve the quality of life of the patients.